Macrophage‐derived extracellular vesicles regulate follicular activation and improve ovarian function in old mice by modulating local environment. Issue 10 (13th October 2022) - Xiao, Yue; Peng, Xiaoxu; Peng, Yue; Zhang, Chi; Liu, Wei; Yang, Weijie; Dou, Xiaowei; Jiang, Yuying; Wang, Yaxuan; Yang, Shuo; Xiang, Wenpei; Wu, Tinghe; et al.
Abstract: In mammals, ovarian function is dependent on the primordial follicle pool and the rate of primordial follicle activation determines a female's reproductive lifespan. Ovarian ageing is characterised by chronic low‐grade inflammation with accelerated depletion of primordial follicles and deterioration of oocyte quality. Macrophages (Mφs) play critical roles in multiple aspects of ovarian functions; however, it remains unclear whether Mφs modulate the primordial follicle pool and what is their role in ovarian ageing. Here, by using super‐ or naturally ovulated mouse models, we demonstrated for the first time that ovulation‐induced local inflammation acted as the driver for selective activation of surrounding primordial follicles in each estrous cycle. This finding was related to infiltrating Mφs in ovulatory follicles and the dynamic changes of the two polarised Mφs, M1 and M2 Mφs, during the process. Further studies on newborn ovaries cocultured with different subtypes of Mφs demonstrated the stimulatory effect of M1 Mφs on primordial follicles, whereas M2 Mφs maintained follicles in a dormant state. The underlying mechanism was associated with the differential regulation of the Phosphatidylinositol 3‐kinase/Mechanistic target of rapamycin (PI3K/mTOR) signaling pathway through secreted extracellular vesicles (EVs) and the containing specific miRNAs miR‐107 (M1 Mφs) and miR‐99a‐5p (M2 Mφs). In aged mice, the intravenous injection of M2‐EVs improved ovarian function and ameliorated the inflammatory microenvironment within the ovary. Thus, based on the anti‐ageing effects of M2 Mφs in old mice, M2‐EVs may represent a new approach to improve inflammation‐related infertility in women. Abstract : Ovulation induced local inflammation environment selectively activates primordial follicles. M1 Mφs have a stimulatory effect on primordial follicles while M2 Mφs maintain them in a dormant state. M2‐EVs in vivo treatment ameliorate the inflammatory microenvironment within the ovary and improve ovarian function in aged mice.